1999
DOI: 10.1016/s0893-133x(98)00060-8
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychopharmacology of Phencyclidine From NMDA Receptor Hypofunction to the Dopamine Hypothesis of Schizophrenia

Abstract: Administration of noncompetitive NMDA ր glutamate receptor antagonists, such as phencyclidine (PCP) and ketamine, to humans induces a broad range of schizophrenic-like symptomatology, findings that have contributed to a hypoglutamatergic hypothesis of schizophrenia. Moreover, a history of experimental investigations of the effects of these drugs in animalsBiological psychiatric research has seen the development of many putative animal models of schizophrenia. The etiological bases of these models have varied w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

32
772
1
19

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,207 publications
(834 citation statements)
references
References 239 publications
32
772
1
19
Order By: Relevance
“…It has been reported that there are qualitative and quantitative differences in the effects of acute vs chronic PCP exposure (Jentsch and Roth, 1999). For example, studies demonstrated that the chronic treatment selected here has been effective previously in inducing durable cognitive dysfunction, social withdrawal, and enhancement of immobility time in the forced swim test in rats or mice that are not observable after acute PCP (Noda et al, 1995(Noda et al, , 2000Jentsch et al, 1997c;Quiao et al, 2001).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been reported that there are qualitative and quantitative differences in the effects of acute vs chronic PCP exposure (Jentsch and Roth, 1999). For example, studies demonstrated that the chronic treatment selected here has been effective previously in inducing durable cognitive dysfunction, social withdrawal, and enhancement of immobility time in the forced swim test in rats or mice that are not observable after acute PCP (Noda et al, 1995(Noda et al, , 2000Jentsch et al, 1997c;Quiao et al, 2001).…”
Section: Introductionmentioning
confidence: 92%
“…Further it has been hypothesized that the negative symptoms of schizophrenia, such as anhedonia and avolition (ie lack of motivation; American Psychiatric Association, 1994) may be neurobiologically similar to depressive symptomatology, such as anhedonia and dysphoria, seen in both drug-and nondrug-induced depressions (Markou and Kenny, 2002). Withdrawal from PCP treatment induces in humans and rodents some longlasting behavioral and neurochemical perturbations that have been hypothesized to have relevance to schizophrenia symptomatology and neuropathologies, respectively (Jentsch and Roth, 1999). These observations have led to the hypothesis of hypofunctioning of the glutamatergic system as one of the pathophysiologies mediating schizophrenia (Javitt and Zukin, 1991;Carlsson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCP and its structural analogue ketamine produce inactivation of inhibitory control by decreasing GABA release [58]. This disinhibition of excitatory neurotransmission is referred to as NMDA receptor hypofunction [32,45,46]. Acute administration of PCP in rats has been shown to produce deficits in the novel object recognition-NOR-task [21], an operant reversal learning paradigm [1,28] and attentional set-shifting [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we employed the well-validated subchronic phencyclidine (PCP)-administration paradigm (Jentsch and Roth, 1999;Cochran et al, 2003;Egerton et al, 2005;Abdul-Monim et al, 2006, 2007 to produce enduring cognitive deficits similar to those observed in schizophrenia (Javitt and Zukin, 1991). This permitted us to examine treatment effects of classical and second-generation antipsychotics that have different profiles and activity at multiple neurotransmitter receptors, including dopamine (DA) D 2 , 5-HT 2A , and 5-HT 6 .…”
Section: Introductionmentioning
confidence: 99%